Drought and Sub-Saharan African Economies - Benson, Charlotte; Clay, Edward (World Bank, Washington, DC, 2012)
Droughts are frequent and severe in many countries of Sub-Saharan Africa (SSA) and have a devastating impact on their peoples and economies. The extreme vulnerability to rainfall in the arid and semiarid areas of the continent and the poor capacity of most African soils to retain moisture result in almost 60 percent of SSA being vulnerable to drought and 30 percent being extremely vulnerable. Since the 1960s, rainfall in parts of the Sahel and Southern Africa has also been significantly below the norms of the previous 30 years. Moreover, the prospects of an El Nino effect has led to more focus on the impact of drought in SSA. Against the background of a dearth of investigative studies on drought's economic impact, a recent report, the impact of drought on Sub-Saharan African economies: a preliminary examination examines this phenomenon more closely. Drought has typically been perceived as a problem principally of agriculture and, in particular, food supply. As such, it is seen as posing problems for effective relief but there is less evidence on whether or not it justifies economic responses or modifications in policy. This report presents the findings of an exploratory study which was intended as a contribution to filling that gap. Analysis of a number of issues pulls together lessons learned from six country cases (Burkina Faso, Ethiopia, Kenya, Senegal, Zambia, and Zimbabwe) to develop strategies to reduce the economy-wide impacts of drought.